Head Trauma in a Community-Based Sample of Victims of Intimate Partner Violence: Prevalence, Mechanisms of Injury and Symptom Presentation - Meyer, Jessica E. (Journal of interpersonal violence, 2022)
Objective.The present study aimed to explore the prevalence of subconcussive head trauma, traumatic brain injury (TBI), potential hypoxic events, and hypoxic brain injury (HBI) in victims of physical intimate partner violence (IPV). The study also aimed to characterize the injury presentation and mechanisms of injury in this population.Method.A group of 47 female participants with a history of at least one relationship that included physical violence completed a structured interview assessing for subconcussive hits, TBI, and HBI. Participants ranged in age from 19 to 55, and had an average of 15.3 years of education. Forty-four participants completed the structured interview in person and three participants completed the interview over the phone.Results.The majority of participants reported sustaining at least one impact to the head and approximately half of the participants sustained at least one impact that resulted in a mild TBI. Approximately half of the participants experienced at least one incident of having difficulty breathing due to a violent act from their partner, and approximately one-third of participants reported symptoms consistent with mild HBI. The most common mechanisms of injury were being hit with a closed fist and being strangled.Conclusions.The high levels of head trauma observed in this study highlight the need for clinical and community providers to screen victims of physical IPV for head trauma. The unique characteristics of this population (female sex, high frequency of injuries, and presence of HBIs) indicate that research evaluating the cognitive effects of injuries in this population is needed.